Metformin Use in Relation to Clinical Outcomes and Hyperinflammatory Syndrome Among COVID-19 Patients With Type 2 Diabetes: A Propensity Score Analysis of a Territory-Wide Cohort - Wong, Carlos K. H.; Lui, David T. W.; Lui, Angel Y. C.; Low, Marshall C. H.; Kwok, Ashley C. Y.; Lau, Kristy T. K.; Au, Ivan C. H.; Xiong, Xi; Chung, Matthew S. H.; Lau, Eric H. Y.; Cowling, Benjamin J. (Frontiers in Endocrinology, 2022)
Aim: To evaluate the association between metformin use and clinical outcomes in type 2 diabetes mellitus (T2DM) patients hospitalized with COVID-19. Methods: Patients with T2DM with confirmed diagnosis of COVID-19 and admitted between 21st January 2020 and 31st January 2021 in Hong Kong were identified in our cohort. Exposure was defined as metformin use within 90 days prior to admission until hospital discharge for COVID-19. Primary outcome was defined as clinical improvement of ≥1 point on the WHO Clinical Progression Scale (CPS). Other outcomes were hospital discharge; recovery; in-hospital death; acidosis; hyperinflammatory syndrome; length of hospitalization; and changes in WHO CPS score. Results: Metformin use was associated with greater odds of clinical improvement (OR=2.74, p=0.009), hospital discharge (OR=2.26, p=0.009) and recovery (OR=2.54, p=0.005), in addition to lower odds of hyperinflammatory syndrome (OR=0.71, p=0.021) and death (OR=0.41, p=0.010) than control. Patients on metformin treatment had a shorter hospital stay (-2.76 days, p=0.017) than their control counterparts. Average WHO CPS score were significantly lower in metformin users than non-users since day 15 (p<0.001). However, metformin use was associated with higher odds of acidosis. Conclusions: Metformin use was associated with lower mortality and lower odds for hyperinflammatory syndrome. This provides additional insights into the potential mechanisms of benefits of metformin use in T2DM patients with COVID-19.